Design and development of wireless charging system for autonomous/electric vehicles - Teo, Jer Rome (2015)
Depleting fossil fuels and detrimental environmental pollution effects caused by the combustion of these fossil fuels are a major issue that the world faces today. One major sector that contributes to these issues is the transportation sector. To overcome this, technologists, scientists and environmentalists come together in search of alternatives that are environmentally friendly and self-sustaining. One such alternative is the invention of the electric vehicle (EV). The EV is powered by the electrochemical battery. Pure EVs have zero carbon emission and does not require the use of fossil fuels. The on-board battery of the EV is currently charged by the conventional conductive charging method which involves plugging in to the electrical grid. This method is troublesome and poses safety issues such as risk of electric shocks as cables are involved. Wireless charging, widely researched today, is finding its way to the consumer market for EV charging. It boasts hassle-free convenient charging for users and reduces the safety issue aspect that the conventional method faces. However, low efficiency is the key down point of wireless charging due to the energy transmission through an air gap. In addition, to comply with safety standards on human exposure to electromagnetic field (EMF) radiation, methods to minimize the stray EMF such as shielding has to be considered in the design of the charging system. This will increase installation costs. This report presents some the available EVs and their battery specifications in the market today. Various wireless power transfer and wireless charging systems are discussed. Factors that will affect the performance parameters of the wireless charging system are also discussed. In addition, a prototype wireless charging system is designed and developed and its efficiency at different vertical offset distances are recorded.